A Critical Review of the Standards and Design Processes for Motorway Diverges in the UK - Wall, G.T.; Hounsell, N.B. (European Journal of Transport and Infrastructure Research, 2004)
This paper contains a critical review of design standards for motorway diverges in the UK over the last 40 years. These standards have been progressively updated at regular intervals and their evolving nature has been assessed. Most changes have been minor as a result of changes to traffic flow, driver behaviour or vehicle performance. A brief comparison has also been made between standards for diverges in the UK and those in other selected EU countries. This paper particularly focuses on the diverging flow-region diagram contained in the latest Government Standard TD22/92 ‘The Layout of Grade-Separated Junctions’. This diagram is used by traffic engineers as a tool in order to select the most appropriate diverge layout for a particular site. The historical background leading to its derivation is reviewed along with a discussion of comments made by five practicing traffic engineers as to its effectiveness and usage. These comments have been used along with other analysis to make recommendations as to how the diagram should be interpreted and how it could be improved.